A VALUE BASED GO-TO-MARKET STRATEGY TO LIQUIDATE STAGNANT INVENTORY OF NON-SUBSIDIZED ZA FERTILIZERS AT PT PUPUK INDONESIA (PERSERO) - Cendana Biru (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study investigates a critical commercial impasse at PT Pupuk Indonesia (Persero), characterized by the accumulation of 128,590 tons of stagnant non-subsidized ammonium sulfate (ZA) fertilizer, particularly ZA Petro and ZA Plus Petro, in West Java’s agricultural sector. The stagnation is driven by external price resistance, reflected in a retail price gap of IDR 80,000–90,000 compared with generic private competitors, and internal supply-side frictions, including dysfunctional inter-line margin policies, logistics bypassing, and limited field-sales capacity. This study aims to evaluate B2B market realities, diagnose structural weaknesses in supply-chain and channel management, and formulate an actionable non-price defense strategy. A qualitative case study design was employed, focusing on commercial horticulture in West Java. Purposive sampling involved eight strategic informants representing commercial farmers, R1 distributors, and internal logistics personnel across Lines 1 and 3. Data were analyzed using deductive content analysis based on Business Buying Behavior, Business Buying Organization, Product Differentiation, Supply Chain Management, and Channel Management theories. The findings indicate that despite strong agronomic advantages, including 100% water solubility and zinc enrichment exceeding 5,000 ppm, weak local promotion and structural channel conflicts have constrained market penetration. The study proposes a Retail ZA Go-To-Market Playbook integrating STP, 7P interventions, value-based pricing, channel incentives, conditional consignment, and demonstration plots to accelerate inventory liquidation while protecting profitability.